2010
DOI: 10.1080/10286020903436519
|View full text |Cite
|
Sign up to set email alerts
|

New grayanol diterpenoid and new phenolic glucoside from the flowers of Pieris formosa

Abstract: A new grayanol diterpenoid, grayanotoxin XXII (1), and a new phenolic glucoside, benzyl 2-hydroxy-4-O-[beta-xylopyranosyl(1'' --> 6')-beta-glucopyranosyl]-benzoate (2), were isolated from the flowers of Pieris formosa. Their structures were determined on the basis of spectroscopic analysis and chemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The 1,5- seco -grayanane-type of diterpenoids, also known as the grayanol-type, has been considered as the structural intermediate of the grayanane-type (5/7/6/5), leucothane-type (6/6/6/5), and kalmane-type (5/8/5/5). , Biogenetic transformation between the diterpenoids seems prevalent in Ericaceae plants; for instance, Sakakibara et al and Kaiya et al reported that grayanotoxin II can be transformed chemically to the leucothane and grayanol types. , 1,5- seco -Grayanane is a small group that mainly comprises five diterpenoids in natural products. , Grayanotoxin XXII ( 93 ) (Figure ), as one of 1,5- seco -grayananes whose carbon skeleton was possibly rearranged from the grayanane type or leucothane type (Figure ), has been identified in the flowers of P. formosa , and its structure was determined by spectroscopic and chemical analyses …”
Section: 5-seco-grayananes (Grayanol Diterpenoids)mentioning
confidence: 99%
“…The 1,5- seco -grayanane-type of diterpenoids, also known as the grayanol-type, has been considered as the structural intermediate of the grayanane-type (5/7/6/5), leucothane-type (6/6/6/5), and kalmane-type (5/8/5/5). , Biogenetic transformation between the diterpenoids seems prevalent in Ericaceae plants; for instance, Sakakibara et al and Kaiya et al reported that grayanotoxin II can be transformed chemically to the leucothane and grayanol types. , 1,5- seco -Grayanane is a small group that mainly comprises five diterpenoids in natural products. , Grayanotoxin XXII ( 93 ) (Figure ), as one of 1,5- seco -grayananes whose carbon skeleton was possibly rearranged from the grayanane type or leucothane type (Figure ), has been identified in the flowers of P. formosa , and its structure was determined by spectroscopic and chemical analyses …”
Section: 5-seco-grayananes (Grayanol Diterpenoids)mentioning
confidence: 99%
“…Diterpenoids in poisonous plants belonging to the Ericaceae family comprise a few specialized carbon frameworks usually decorated with highly oxygenated chemical groups. The four main compound types are grayanane, leucothane, ent -kaurane, and kalmane. The grayanane-type diterpenoids, derived biogenetically from the ent -kanrane skeleton, predominate in Ericaceae plants. Nearly 130 grayanoids have been identified from the family Ericaceae, and some of them have exhibited remarkable biological activities, such as antifeedant, growth inhibitory, and insecticidal activities. , The grayanane-type diterpenoids are believed to play a mainly defensive role in poisonous plants of Ericaceae family by exhibiting antifeedant and insecticidal activities.…”
Section: Introductionmentioning
confidence: 99%
“…The grayanoid diterpenoids, as the characteristic secondary metabolites of the plants of Ericaceae, have attracted much attention from chemists and biologists not only for their intriguing structure but also for their diverse bioactivity, especially for their toxicity, as well as their analgesic, significant antifeedant, and insecticidal activity [ 3 , 4 , 5 ]. To date, 15 types of diterpenoid skeleton have been reported, including grayanane (A-nor-B-homo ent -kaurane) [ 5 ], 1,5-secograyanane [ 6 ], 3,4-secograyanane [ 7 ], 9,10-secograyanane [ 8 ], 1,10:2,3-disecograyanane [ 9 ], leucothane (A-homo-B-nor grayanane) [ 10 ], kalmane (B-homo-C-nor grayanane) [ 11 ], 1,5-secokalmane [ 12 ], micranthane (C-homo grayanane) [ 13 ], mollane (C-nor-D-homo grayanane) [ 14 ], rhodomollane (D-homo grayanane) [ 15 ], ent -kaurane, 4,5- seco - ent -kauran [ 16 ], pierisketane (A-homo-B-nor- ent -kaurane) [ 17 ], and rhodomollane [ 18 ]. All of these diterpenoid types are assumed to be derived biogenetically from the ent -kanrane skeleton.…”
Section: Introductionmentioning
confidence: 99%